Antibacterial Applications of RGO, Ni(OH)2, NiO and RGO/NiO Nanocomposite Materials - Ayça Tanrıverdi; Saniye Tekerek; Esen Çakmak (Nanochemistry Research, 2025)
In the present study, reduced graphene oxide (RGO), nickel oxide (NiO), nickel hydroxide (Ni(OH)2) and reduced graphene oxide/nickel oxide (RGO/NiO) composites have been prepared by hydrothermal synthesis. The Hummers method was used to synthesise the graphene oxide (GO) used in the preparation of the RGO/NiO composites. The crystal structure of RGO, Ni(OH)2, NiO and RGO/NiO nanoparticles has been investigated using X-ray diffraction (XRD) and their morphological properties have been studied using scanning electron microscopy (SEM). Enterococcus faecalis (ATCC 29212), Klebsiella pneumoniae (ATCC 29544), Salmonella enterica subsp enterica (NCTC 13) and Staphylococcus aureus (ATCC 29213) were selected for this study. All synthesized nanoparticles (RGO, Ni(OH)2, NiO, and RGO/NiO) showed an effective antibacterial effect against pathogenic microorganisms. A lethal effect of the synthesised nanoparticles on microorganisms was observed. The RGO/NiO nanocomposite exhibited the strongest effect. These nanoparticles show promise as a new alternative to conventional antibiotics for the treatment of resistant microorganisms.